2021
DOI: 10.2147/ijgm.s296316
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Research Progress in the Application of Glycosylated Hemoglobin and Glycated Albumin in the Screening and Monitoring of Gestational Diabetes

Abstract: Glycosylated hemoglobin (HbA1C) and glycated albumin (GA) can be used for blood glucose management of a person with diabetes as a result of their convenience and stability. However, there is no corresponding standard for the application of glycosylated hemoglobin and glycosylated albumin in gestational diabetes mellitus (GDM). In this review, we summarize the published research and discuss three aspects of the significance of HBA1C and GA in GDM patients: screening of gestational diabetes mellitus, blood gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…Glycosylated hemoglobin (HbA1c) is a typical glycosylated protein and is widely used in the assessment of glycemic control [9]. It is produced through the interaction of hemoglobin and blood glucose and can be used to reflect the average blood glucose level over 2-3 months [10]. Several studies in Asia have demonstrated that HbA1c was positively associated with NAFLD status among participants without diabetes [11][12][13][14], but little is known about western populations and whether a special population exists among different subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…Glycosylated hemoglobin (HbA1c) is a typical glycosylated protein and is widely used in the assessment of glycemic control [9]. It is produced through the interaction of hemoglobin and blood glucose and can be used to reflect the average blood glucose level over 2-3 months [10]. Several studies in Asia have demonstrated that HbA1c was positively associated with NAFLD status among participants without diabetes [11][12][13][14], but little is known about western populations and whether a special population exists among different subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…We systematically analyzed the changes in serum leptin levels in different T2DM-related indicators and T2DM complications, and further analyzed the changes of biochemical indicators in T2DM patients with different leptin levels and the prevalence rates of complications of T2DM. In general, HbA1c, as the gold standard for the diagnosis of T2DM, reflects the blood glucose control level of T2DM patients for 2-3 months [35,36], GSP and GA reflect the blood glucose control level of T2DM patients for 2-3 weeks [37,38]. Poor long-term blood glucose control will inhibit insulin secretion through glucose toxicity, and the inhibition of insulin secretion may also lead to low leptin levels [33].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Hashimoto et al., GA levels remained stable throughout pregnancy, whereas HbA1c levels decreased during late gestation and were inversely correlated with ferritin levels and transferrin saturation ( 97 ). An accurate GA threshold for diagnosing GDM remains elusive, and the application of GA as a screening tool for GDM is therefore controversial ( 101 , 102 ). The use of GA for GDM diagnosis has not been investigated in pregnant South-African women.…”
Section: Diagnostic Tests and Criteriamentioning
confidence: 99%